EFFECTIVE WAYS TO FEED BEES IN DIFFERENT HIVES IN THE COUNTRY (ResearchJet Journal of Analysis and Inventions, 2023)
In the article, the world of a salari has attracted mankind for several thousand years. Bees are the most useful insects that live as a family, which play a key role in pollinating plants. They can be found in all parts of the earth's crust. For centuries, mankind has been using honey, bee food, bee milk, bee venom, bee wax, and propolis, as well as a goddessnetwork in this regard ways of development.